Language Contact in Judea?: Hebrew, Aramaic, and Punic - Mor, Uri (Dead Sea discoveries, 2014)
This paper examines a set of linguistic parallels between Judean Hebrew and Aramaic, on the one hand, and Punic and Late Punic, on the other, in order to examine J. T. Milik’s 1957 claim for a Hebrew-Phoenician koine in southern Palestine. The analysis of the evidence indeed indicates language contact (rather than parallel development), but does not support Milik’s notion of a southern koine.